OER Research toolkit - Hilton, John, III; Brigham Young University. Open Education Group; BC Open Textbook Project; BCcampus (Open Education Group, 2017)
"The OER Research Toolkit is comprised of the OER Research Guidebook and several additional resources. The purpose of this guidebook is to provide ideas for how individual faculty members and those who support them (e.g., librarians, instructional designers, etc.) can research the effect of their adoption of open educational resources (OER). Clearly educational research is a challenging enterprise; this guidebook is not meant to replace the substantive courses and experiences that a PhD in educational research would provide. Rather, our hope is to provide some straightforward suggestions that could be implemented by OER adopters so as to help them identify what has happened as a result of their OER adoption. This is a creation of the OER Research Guidebook and was generously supported by the Open Textbook Network"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on August 18, 2017).
Keywords: Teaching -- Aids and devices -- Textbooks; Electronic books